Síntese de adutos de Morita-Baylis-Hillman simétricos derivados de isatina com atividade anticâncer e leishmanicida - Coelho, Maísa Cavalcanti (2023)
Two important questions in human health, cancer and leishmaniasis have usual treatments that include injectable medicine with a lot of adverse effects, high cost and sometimes ineffective. In the context of need of new drugs development, the 3-hydroxy-2-oxindol scaffold is present in synthetic molecules with antiproliferative and leishmanicidal properties. In order to synthetize this nucleus, the Morita-Baylis-Hillman reaction (MBHR) can be used, and some adducts are already reported as anti-leishmania and antitumor. With the purpose of enhancing this activity, we used a molecular dimerization approach in the design of the novel molecules. The aim of this work was to obtain new dimmeric Morita-Baylis-Hillman adducts with potential antiproliferative and antiparasitic activity, containing the 3-hydroxy-2-oxindol nucleus formed by Morita-Baylis-Hillman reaction, using isatin as substrate. The synthetic route involved the synthesis of 10 isatin derivatives, the ethyleneglycol acrylate and the MBHR synthesis, forming the dimmeric Morita-Baylis-Hillman Adducts (MBHA). Variables as solvent, temperature, different catalysts and increasing proportions of DABCO (25 to 100%) were tested in the MBHA synthetic optimization. The novel dimmers were characterized by mass spectrometry, Fourier transform infrared (FTIR), 1H and 13C Nuclear Magnetic Resonance (NMR). Room temperature, DABCO 100 mol% and DMF were chosen as the best reaction conditions, with 43% yield in the case of the dimer used in the optimization study (1a, N-metilado). The reaction time varyied between 15 minutes to 11 days, and yields between 24 and 67%. 10 original dimmers were biologically evaluated in the cancer cell lines K-569, HL-60 e A-549 and also in promastigotes and amastigotes of Leishmania infantum. Among the adducts sent to antiproliferative evaluation, 1h, a Nbenzilated and dichlorated dimmer, presented strong activity against all the strains (IC50 0,72 to 2,24 μM and SI 0,6 to 1,87), as well 1f, a N-metilated and dichlorated dimmer (IC50 1,18 to 3,83 μM and SI 1,8 a 5,84), being both considered promising. The dimmers of this work (IC50 1,18 to 7,94 μM) were more active than the existing correspondent monomers (IC50 4,2 to 16,08 μM) reported in the literature, evidencing the efficacy of dimmerization approach in this case. The in vitro tests in Leishmania infantum showed 1h and 1f as the most active too, with IC50 of 5,48 and 5,7 μM, respectively, in the amastigote form of the parasite.